Behavior and Response of Headed Stud Connectors in Composite Steel Plate Girder Bridges under Cyclic Lateral Deformations - Hamid Bahrami, Eric V. Monzon (Engineering Journal, 2015)
Most of the mass of steel plate girder bridge superstructures is concentrated in the reinforced concrete deck. During a seismic event, the inertia force that is generated in the reinforced concrete deck is transferred to the support cross frames through the headed stud connectors. Seismic analyses showed that these connectors are subjected to combined axial tension and shear forces. If not designed properly, these connectors may fail prematurely during an earthquake, altering the load path and subjecting other bridge components to forces they are not designed for. To verify these observations, two half-scale models of plate girder bridge subassembly were constructed and subjected to cyclic testing. The two specimens represented two different configurations of headed stud connectors in transferring the deck seismic forces. The connectors in the first specimen connected the girder top flange to the reinforced concrete deck, while the connectors in the second specimen connected the cross-frame top chord to the deck. These experiments showed that the connectors were indeed vulnerable under transverse lateral loading. The failure mode of these connectors is a combination between shear and tensile forces or concrete breakout. Based on this investigation, design equations were proposed and adopted in the AASHTO LRFD Bridge Design Specifications to evaluate the resistance of such connectors under shear and tensile forces.